2019
DOI: 10.1103/physreve.100.023117
|View full text |Cite
|
Sign up to set email alerts
|

Taylor-vortex flow in shear-thinning fluids

Abstract: The present paper deals with the Taylor-Couette flow of shear-thinning fluids. It focuses on the first principles understanding the influence of the viscosity stratification and the nonlinear variation of the effective viscosity µ with the shear rateγ on the flow structure in the Taylor vortex flow regime. A wide gap configuration (η = 0.4) is mainly considered. A weakly nonlinear analysis, using the amplitude expansion method at high order is adopted as a first approach to study nonlinear effects. For the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The spatial wavelength of the TVF has been found to increase with increased shear-thinning, as observed in experiments and the linear stability analysis by Bahrani et al (2015) (in a large gap flow cell), laser Doppler velocimetry measurements by Escudier et al (1995) or particle image velocimetry (known as PIV) in Cagney & Balabani (2019b). From the two later works and numerical simulations by Topayev et al (2019) and Alibenyahia et al (2012), shear-thinning was found to modify the structure of the Taylor vortices, by making individual vortices asymmetric, and increasing the amplitudes of the travelling waves at the inward and outward jets. Sparse data on the critical Re value for the TVF to WTVF (Bahrani et al 2015;Cagney et al 2020) suggest that the TVF to WTVF transition happens at lower Re values with increased shear-thinning.…”
Section: Shear-thinning Tcfs With Negligible Elasticitymentioning
confidence: 76%
See 4 more Smart Citations
“…The spatial wavelength of the TVF has been found to increase with increased shear-thinning, as observed in experiments and the linear stability analysis by Bahrani et al (2015) (in a large gap flow cell), laser Doppler velocimetry measurements by Escudier et al (1995) or particle image velocimetry (known as PIV) in Cagney & Balabani (2019b). From the two later works and numerical simulations by Topayev et al (2019) and Alibenyahia et al (2012), shear-thinning was found to modify the structure of the Taylor vortices, by making individual vortices asymmetric, and increasing the amplitudes of the travelling waves at the inward and outward jets. Sparse data on the critical Re value for the TVF to WTVF (Bahrani et al 2015;Cagney et al 2020) suggest that the TVF to WTVF transition happens at lower Re values with increased shear-thinning.…”
Section: Shear-thinning Tcfs With Negligible Elasticitymentioning
confidence: 76%
“…While this analysis has been based on a purely azimuthal CF, the radial viscosity gradient due to the main shear in the gap persists even for higher-order flows. For example in Cagney & Balabani (2019b) and Topayev et al (2019), it is shown that Taylor vortices are squeezed and deform against the inner cylinder, in the lower viscosity inner region (Topayev et al 2019). The previous scaling arguments on enhanced elasticity parameters are thus likely to hold in more complex flows as well due to the base mean shear.…”
Section: What Are the Mechanisms Of Shear-thinning Mediation?mentioning
confidence: 84%
See 3 more Smart Citations